(untitled) (SCIENCE TIME JOURNAL, 2026)
This article examines the use of stylistic devices in reporter speech within contemporary media discourse. Media discourse is not only a means of transmitting information but also a complex communicative environment in which social meanings, ideological attitudes, emotional evaluations, and pragmatic intentions are constructed. In this process, the reporter plays a central role as a mediator between an event and the audience. The language of the reporter is expected to be clear, informative, objective, and socially responsible; however, it also contains a wide range of stylistic devices that enhance expressiveness, attract audience attention, and shape the interpretation of events. The article analyzes lexical, syntactic, phonetic, and pragmatic stylistic devices commonly used in reporter speech, including metaphor, epithet, comparison, repetition, parallelism, rhetorical questions, inversion, ellipsis, emotional-evaluative vocabulary, and intonational emphasis. The study demonstrates that stylistic devices in reporter speech perform informative, evaluative, persuasive, emotional, and text-organizing functions. At the same time, their use must be balanced with the principles of journalistic accuracy, neutrality, and ethical responsibility.